Higher-Order Musical Temporal Structure in Bird Song - Bilger, Hans T.; Vertosick, Emily; Vickers, Andrew; Kaczmarek, Konrad; Prum, Richard O. (Frontiers in Psychology, 2021)
Bird songs often display musical acoustic features such as tonal pitch selection, rhythmicity, and melodic contouring. We investigated higher-order musical temporal structure in bird song using an experimental method called "music scrambling" with human subjects. Recorded songs from a phylogenetically diverse group of 20 avian taxa were split into constituent elements ("notes" or "syllables") and recombined in original and random order. Human subjects were asked to evaluate which version sounded more "musical" on a per-species basis. Species identity and stimulus treatment were concealed from subjects, and stimulus presentation order was randomized within and between taxa. Two recordings of human music were included as a control for attentiveness. Participants varied in their assessments of individual species musicality, but a highly significant preference for original order bird songs over temporally randomized ones was found across all 20 taxa. We discuss alternative hypotheses for the origins of avian musicality, including honest signaling, perceptual bias, and arbitrary aesthetic coevolution.